Drawing the dome. The center of Malagueira. - Guilherme, Pedro (2020)
This paper analyses the instrumentality of Alvaro Siza’s drawings in his architectural practices at the specific case of Malagueira (Évora, Portugal, 1977-2005). Malagueira acts as a major urban project that entails the practice of architecture: the urban plan, the landscape design, housing and public equipment’s, and detailed design. Álvaro Siza’s “cadernos” (drawing books) are research objects that unveil the conscient mind of the architect and drawing provides specific approaches to mainstream architecture. Although the primary role of drawing practice is to represent architectural concepts, the drawing is not merely an analytical and interpretative means of spatial representation, but an empirical tool, for visual thinking and the visual imagining of space. Thus, it acts as a research tool within design that can be analysed and conveyed as a methodological approach for researching “into”, “through”, and “for” architecture. Siza’s drawings provide spatial experiences and give particular attention to the viewer: thru the hand of the architect (drafter) a user’s perspective (hypothesis) is tested and verified. The continuas and relentless, almost compulsory, drafting of hypothesis and the incorporation of ambiguous and external influences creates a corpus of design that influences the end piece of the project.